Regional Variations in Farming Household Structure for the Swedish Elderly, 1890–1908. (October 2016) - Magnuson, Mark
The theoretical Northwest European family structure does not sufficiently represent the variation found among elderly people in rural Sweden during the decades leading up to the National Pension Act of 1913. These regional variations in family types are broadly contextualized using simple but effective measures, which include simple high/low clustered analysis of the percentage of individuals over sixty in farming households with no children or grandchildren. This study presents a significant relationship between elderly family structure, levels of participation in household retirement contracts, elderly receiving public assistance, and to economic and ecological factors that have been hypothesized in prior research.